Clinical Characteristics of Patients with Clostridium Difficile Infection and Its Relationship with Fecal Occult Blood Test - Şenel, T.; Ayyildiz, T. (Ondokuz Mayis University, 2021)
Clostridium difficile infection (CDI) is an important health problem with severe morbidity and mortality. In our study, 266 adult patients admitted to the hospital between the years 2005 and 2020, and were diagnosed with CDI were included. The relationship between CDI and fecal occult blood test (FOBT) was examined, and it was aimed to determine the clinical characteristics of CDI patients and risk factors for mortality and recurrence in these patients. FOBT was found to be positive in 42.8% of our CDI patients who underwent FOBT. Pseudomembranous enterocolitis (PME) developed in 2.2% and toxic megacolon developed in 0.8% of our patients. It was found that 10.2% of the CDI patients died within 30 days and 5.2% of the CDI patients had a recurrence. In our study, a significant relationship was found between mortality and advanced age, FOBT negativity, presence of hospitalization history. In addition, a significant relationship was found between recurrence and FOBT positivity, presence of PME. We believe that the data documented in this study are important because these data reveal both the clinical characteristics of CDI patients and its relationship with FOBT. © 2021 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: Clostridium difficile Infection; Fecal Occult Blood Test; Pseudomembranous Enterocolitis; Toxic Megacolon